2019
DOI: 10.3390/ijms20163923
|View full text |Cite
|
Sign up to set email alerts
|

A Long Polymorphic GT Microsatellite within a Gene Promoter Mediates Non-Imprinted Allele-Specific DNA Methylation of a CpG Island in a Goldfish Inter-Strain Hybrid

Abstract: It is now widely accepted that allele-specific DNA methylation (ASM) commonly occurs at non-imprinted loci. Most of the non-imprinted ASM regions observed both within and outside of the CpG island show a strong correlation with DNA polymorphisms. However, what polymorphic cis-acting elements mediate non-imprinted ASM of the CpG island remains unclear. In this study, we investigated the impact of polymorphic GT microsatellites within the gene promoter on non-imprinted ASM of the local CpG island in goldfish. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…TG/CA microsatellites are the most abundant dinucleotide repeats in the human genome [4,8,12]. They exhibit multifaceted functional roles, such as modulation of gene expression [26], recombination [11] and intron splicing due to their polymorphic nature [27]. Therefore, a comparative study of these repeats in primate genomes, which originated from a common ancestor, is likely to provide useful insights into their conservation and evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TG/CA microsatellites are the most abundant dinucleotide repeats in the human genome [4,8,12]. They exhibit multifaceted functional roles, such as modulation of gene expression [26], recombination [11] and intron splicing due to their polymorphic nature [27]. Therefore, a comparative study of these repeats in primate genomes, which originated from a common ancestor, is likely to provide useful insights into their conservation and evolution.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted May 9, 2023. ; https://doi.org/10.1101/2023.05.09.539941 doi: bioRxiv preprint showed that long polymorphic TG repeats can alter methylation of downstream CpG island in goldfish models [26]. (TG/CA) repeats also play a role in intron splicing as shown by a study conducted by Hui et al, where they showed that length of CA repeats can alter splicing efficiency by serving as HnRNP L recruitment site during intron splicing in eNOS gene [27].…”
Section: Introductionmentioning
confidence: 99%